Documentation of Wild Medicinal Plants and Agricultural Crop in the part of Doon Valley, Uttarakhand, India - Bhatt, Ganesh Datt; Rana, Deepali; Singh, Mahesh (Indian Forester, 2021)
The present study was conduct to document wild medicinal plants and agriculture crops which are growing in and around Selaqui, district Dehradun, Uttarakhand, India. Number of field trips was undertaken for a period of two years from November, 2016 - October, 2018 to enumerate the wild medicinal plants and agriculture crops. The wild medicinal plants were collected from different parts of Selaqui at regular intervals for plant taxonomy. On the basis of field surveys, a total of 129 plant species have been collected, identified and listed. The list comprises of plants belongs to cereals, millets, legumes, root vegetables, stem vegetables, herbage vegetables, fruit vegetables, fruits, fibers, wood, wild medicinal plants and oil crops. The recorded plant species are divided into two groups namely, agro-horti crops and wild medicinal plants. The botanical names, families along with English and Hindi names have been updated as per existing flora. It was observed that the agricultural and horticultural crops were represented by a total of 77 representatives whereas wild medicinal plants were represented by 52 species. The results showed that family Leguminosae is dominant with the maximum number of species (19) followed by Poaceae (11) and Amaranthaceae (7). The study reveals that these plant species form minor but important food component for the local people and rural communities. The study also focused on the involvement of natural medicinal flora harvest foodstuff to entire foodstuff and dietary safety measures of inhabitant community has been undervalue.